THE IMPACT OF NEW CORONAVIRUS INFECTION COVID-19 ON WOMEN'S REPRODUCTIVE HEALTH - Яна Андреевна Парфенова; Нонна Марковна Шибельгут; Наталья Владимировна Артымук (The Publishing House Medicine and Enlightenment, 2021)
The aim of the study - assess the impact of COVID-19 on women's reproductive health and identify the relationship between its severity and the incidence of menstrual disorders. Materials and methods. Study design: single-point cross-section. Research method: interviewing by phone, copying data from medical records of an inpatient patient. F003/U. The research included 83 women who received hospital treatment concerning NCI COVID-19. Statistical processing of the obtained data was carried out using the application package «Microsoft Excel 2007». Conclusion. The NCI COVID-19 has a negative impact on women's reproductive health. Further in-depth research is needed in this direction.